2009
DOI: 10.1117/12.815529
|View full text |Cite
|
Sign up to set email alerts
|

Energy harvesting and wireless energy transmission for embedded sensor nodes

Abstract: In this paper, we present experimental investigations using energy harvesting and wireless energy transmission to operate embedded structural health monitoring sensor nodes. The goal of this study is to develop sensing systems that can be permanently embedded within a host structure without the need for an on-board power source. With this approach the required energy will be harvested from the ambient environment, or periodically delivered by a RF energy source to supplement conventional harvesting approaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In previous studies, such a test fixture was tuned to match the fundamental frequency observed in the vibration response of the Omega Bridge, located in Los Alamos, NM [18]. A more detailed description of the energy harvester, including its analytical model and experimental verification has previously been presented by the authors [18]. Researchers have also worked to develop broadband vibrational energy harvesters [9].…”
Section: Energy Harvestingmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous studies, such a test fixture was tuned to match the fundamental frequency observed in the vibration response of the Omega Bridge, located in Los Alamos, NM [18]. A more detailed description of the energy harvester, including its analytical model and experimental verification has previously been presented by the authors [18]. Researchers have also worked to develop broadband vibrational energy harvesters [9].…”
Section: Energy Harvestingmentioning
confidence: 98%
“…While commercially available parabolic grid antennas are still useful for transmission, custom microstrip patch antenna arrays designed by our group in both 2.4GHz and 5.8GHz frequency bands significantly outperform commercially available designs on a per receiving area basis [18,19]. A more detailed description of the individual patch antenna arrays can be found in the references [18,19].…”
Section: Rf Energy Transmission Test Setupmentioning
confidence: 98%
See 1 more Smart Citation
“…Aluminum blocks (2.5cm x 2.5cm x 2.5cm) were added as a tip mass to reduce the natural frequency of the test sample, increasing the transverse displacement of the cantilevered beam (and thereby the strain in the PZT), while maintaining a higher frequency to maintain efficient energy conversion. In previous studies, such a test fixture was tuned to match the fundamental frequency observed in the vibration response of the Omega Bridge, located in Los Alamos, NM [12]. A more detailed description of the energy harvester, including its analytical model and experimental verification has previously been presented by the authors [12].…”
Section: Energy Harvesting Test Setupmentioning
confidence: 99%
“…In previous studies, such a test fixture was tuned to match the fundamental frequency observed in the vibration response of the Omega Bridge, located in Los Alamos, NM [12]. A more detailed description of the energy harvester, including its analytical model and experimental verification has previously been presented by the authors [12].…”
Section: Energy Harvesting Test Setupmentioning
confidence: 99%